Adequacy of authors' replies to criticism raised in electronic letters to the editor: cohort study. (10th August 2010) - Gøtzsche, Peter C; Delamothe, Tony; Godlee, Fiona; Lundh, Andreas
Abstract : Objective To investigate whether substantive criticism in electronic letters to the editor, defined as a problem that could invalidate the research or reduce its reliability, is adequately addressed by the authors. Design Cohort study. Setting BMJ between October 2005 and September 2007. Inclusion criteria Research papers generating substantive criticism in the rapid responses section on bmj.com. Main outcome measures Severity of criticism (minor, moderate, or major) as judged by two editors and extent to which the criticism was addressed by authors (fully, partly, or not) as judged by two editors and the critics. Results A substantive criticism was raised against 105 of 350 (30%, 95% confidence interval 25% to 35%) included research papers, and of these the authors had responded to 47 (45%, 35% to 54%). The severity of the criticism was the same in those papers as in the 58 without author replies (mean score 2.2 in both groups, P=0.72). For the 47 criticisms with replies, there was no relation between the severity of the criticism and the adequacy of the reply, neither as judged by the editors (P=0.88 and P=0.95, respectively) nor by the critics (P=0.83; response rate 85%). However, the critics were much more critical of the replies than the editors (average score 2.3 v 1.4, P<0.001). Conclusions Authors are reluctant to respond to criticisms of their work, although they are not less likely to respond when criticisms are severe. Editors should ensure that authors take relevant criticism seriously and respond adequately to it.